Polyfluoroalkoxyaluminates and borates as new weakly coordinating anions and as components of battery electrolytes - Nolan, Benjamin G., author; Strauss, S. H., advisor (Colorado State University. Libraries, 2001)
The synthesis and characterization of salts of new weakly coordinating anions based on the general formulas B(O2Lf)2– and Al(ORf)4– are reported. New B(O2Lf)2– anions are B(OC(2-C6H4O)(CF3)2)2–, B(OC(2–(O)-3-C6H3F)(CF3)2)2–, B(OC(2-(O)-4-C6H3F)(CF3)2)2–, B(OC(2-(O)-5-C6H3F)(CF3)2)2– B(OC(2-(O)-3,5-C6H2F2)(CF3)2)2–, B(OC(2-(O)-4,5-C6H2F2)(CF3)2)2–,B(OC(2-(O)-4,6-C6H2F2)(CF3)2)2–, B(OC(2-(O)-3,4,5-C6HF3)(CF3)2)2–, B(OC(2-(O)-4,5,6-C6HF3)(CF3)2)2–, B(OC(2-(O)-3-t-Bu-5-Me-C6H2)(CF3)2)2–, B(OC(2-(O)-3,5-C6H2(t-Bu)2)(CF3)2)2–, B(OC(2-(O)-3-C6H3I)(CF3)2)2–. Except for HOC(2-C6H4(OH))(CF3)2, HOC(2-(OH)-4-C6H3F)(CF3)2, and HOC(2-(OH)-3,5-C6H2(t-Bu)2)(CF3)2, all of the diols used as ligand precursors in the new borate anions are new compounds. The new LiAl(ORf)4 salts prepared are LiAl(OCH(CF3)2)4, LiAl(OC(cyclo-C6H11)(CF3)2)4, and LiAl(OC(C6H5)(CF3)2)4. Four Li+ salts of the new borates and aluminates were structurally characterized by X-ray crystallography: Li(OC(CH3)2)(B(OC(2-(O)-3,4,5-C6HF3)(CF3)2)2, Li2(CH3O(CH2)2OCH3)(B(OC(2-C6H4O)(CF3)2)2), LiAl(OCH(CF3)2)4, and LiAl(OC(cyclo-C6H11)(CF3)2)4. Conductivities of solutions of many of the new salts were determined for the solvents 1,2-dimethoxyethane, tetrahydrofuran, propylene carbonate, acetonitrile, and various mixtures of ethylene carbonate and dimethyl carbonate. Conductivities were also measured for the first time for the known salts LiAI(OC(CH3)(CF3)2)4, LiAl(OCH(C6H5)(CF3)2)4, LiAl(OC(4-C6H4(CH3)(CF3)2)4, LiAl(OC(4-C6H4(t- Bu))(CF3)2)4, LiAl(OC(C6H5)(CF3)2)4, and LiAl(OC(CF3)3)4. Based on these measurements, it was determined that all of the anions are more weakly coordinating and more weakly ion-pairing than the commonly-used weakly coordinating anion CF3SO3–. For the B(O2Lf)2– anions, it was found that the ion-pairing strength depends not only on the number of fluorine atoms incorporated into the phenyl groups in the anions but also on their relative positions. Maximum conductivities in 1,2-dimethoxyethane (DME) solution were also determined for several lithium salts, and these exceed the minimum value for practical use in lithium batteries. The maximum value for any LiB(O2Lf)2 salt studied was observed for a 0.5 M DME solution of LiB(OC(2-(O)-4 ,5,6-C6HF3)(CF3)2)2 (8.39 mS cm–1 ). The maximum value for the LiAl(ORf)4 salts studied was observed in a 0.5 M solution of LiAl(OCH(CF3)2)4 (11.2 mS cm–1). Electrochemical stabilities (oxidative, reductive, aluminum corrosion) of the new lithium salts were also examined, and it was found that in almost every case all requirements for practical use were satisfied. The solubility in hexane of LiAl(ORf)4 salts was determined for LiAl(OCH(CF3)2)4, LiAl(OC(C6H5)(CF3)4, LiAl(OC(C6H5)2(CF3))4, LiAl(OC(cyclo-C6H11)(CF3)2. LiAl(OC(CH3)(CF3)2)4, LiAl(OC(4-C6H4(CH3))(CF3)2)4, and LiAl(OC(4-C6H4(t-Bu))(CF3)2)4. Some trends according to ligand type and coordination environment were suggested. Three other classes of weakly coordinating anions were studied in terms of the conductivities of their lithium salts in 1,2-dimethoxyethane, tetrahydrofuran, and propylene carbonate: B(C6F5)3(ORf)– (ORf = OCH(CF3)2, OC(C6H5)2(CF3), OC(CF3)3); carborane anions (CB11H12–, 7,8,9,10,11,12-CB11H6Br6–, 1-CH3-CB11F11–); and the anion based on the hydrogen-bonded complex of CF3CO2– and CF3COOH, H(CF3CO2)2–.
Keywords: chemistry; energy; inorganic chemistry